Economic Effects of Regulatory Reform in Korea - Jungwook Kim; Subok Chae (KDI Journal of Economic Policy, 2017)
This paper adapts the World Bank Regulatory Quality Index (RQI), which is produced annually to provide a better understanding of the effects of regulatory reforms, instead of the Production Market Regulation (PMR) indicators, which are published every five years. We find that 9.9 to 36.0 billion USD worth of regulatory cost could be reduced if the regulatory quality in Korea improves to the level of the OECD average considering that the total burden of regulation in Korea is estimated to range from 2.2 to 357.4 billion USD. The estimated reduction in the regulatory cost accounts for roughly 0.76 to 2.47% of Korea's GDP in 2013, underscoring the importance of regulatory reforms for the Korean economy. This paper introduces a new method with which to examine the distribution of regulatory costs across different industries and firm sizes. This alternative method is largely consistent with the conclusions reached by other studies, specifically that small firms typically bear a disproportionate regulatory burden.
Keywords: K20; L25; O43; 330; Regulatory Quality Index; Regulatory Reform; Economic Impact Analysis